Cybrarian: The Librarian of Future Digital Library - Tulima Dey (International Journal of Informatioan Dissemination and Technology, 2012)
Now a day Libraries are without wall, that all resources of libraries are on digital form accessible through networking communication to remote areas. Present librarian have a skill on handling and manage digital resources and creating institutional database and maintain all e-resources in helpful way to satisfy the user and providing their seeking information in least time as possible. Working in this environment traditional librarian are changing their role drastically and facing several challenges in their professional ground and adopting themselves to new situation. This paper highlighting on this phase that is mobilization of librarian to Cybrarian.
This article discussed the development of digital libraries, in particular, the changing roles of library professionals and changing services of digital libraries. A new concept "cybrarian" was further explicated as well, exploring how librarians could act in era of future digital libraries. Additionally, both professional and personal competencies were identified as requirements for future librarians, especially in future virtual library environment.